Production Step-Up of an Oil Well through Nodal Analysis - Ricardo Michael Kamga Ngankam; Eric Donald Dongmo; Madeleine Nitcheu; Josephine Fleur Matateyou; Gabriel Kuiatse; Sifeu Takougang Kingni (Journal of Engineering)
A nodal analysis technique is used in this paper to optimize the production of oil in the well “X-3” located in the Rio del Rey basin. Several wells in that basin are facing a low productivity problem. That problem represents the key problem of this paper. The goals of this paper are to quantify the effects of four parameters (tubing size, flowline size, wellhead pressure, and skin) on production; to determine the causes of abnormally reduced productivity; and to choose optimal values to enhance the well flow rate. To achieve these goals, it is necessary to use well pressure volume temperature (PVT) and reservoir data and the nodal analysis technique. The nodal analysis method is applied at two main node points (wellbore and wellhead), where inflow and outflow performances are carefully reviewed with sensitivity analysis. The two nodal points are selected because of the high-pressure drops they observe. The analysis results showed that the selection of some wrong equipment diameters (production tubing and surface flowline) and values (wellhead pressure and skin) strongly influenced (badly) the flow rate. In fact, the increase in tubing and flowline diameters positively influenced the flow velocity, while the diminution in the wellhead pressure increased the flow rate as well. The production of the well increased from about 800 to 1000 barrels per day. Although nodal analysis remains an effective method to determine the causes of low productivity, it is limited compared to transient tests and production logging.